De-duplication with Authorization in Hybrid Cloud Approach for Security - Guljar P, Shaikh (International Journal of Computer Sciences and Engineering, 2025)
In cloud computing, most of the communication is done in consideration of file processing, and therefore it turn out to be very critical and important to deliver competent method for data security. The main focus in on data deduplication to provide security services over cloud for stored files. Data deduplication is data compression that is used to eliminate the matching copies of echoing data. This procedure is frequently used for reducing the storage space and save bandwidth over cloud. The term deduplication used for data security and privacy offers to the stored data files, Also encryption methods are applied to stored file information for more security purpose. In this paper we have studied the authorized data deduplication technique for providing security by using user’s differential privileges. Novel deduplication structures are offered for supporting authorized duplicate check. This paper shows how the security is achieved in hybrid cloud throughout the data deduplication process.